New species of Concavapsocus (Psocodea: Psyllipsocidae) from the mid-Cretaceous amber of Myanmar - Yang, Xiao-Yue; Li, Sheng; Ren, Dong; Yao, Yun-Zhi (Zootaxa, 2025)
A new species of Psyllipsocidae, Concavapsocus valvaculeiformus sp. nov., is described from mid-Cretaceous Kachin amber in Myanmar. The key diagnostic distinctions separating the new species from its congeners encompass: 1) the presence/absence of the ecdysial cleavage line and paraproct anal spine; 2) the number of apical teeth on the lacinia; and 3) the morphological characteristics of the female ovipositor valves. This discovery underscores the necessity for revising the generic diagnosis of Concavapsocus, and provides an updated key to the genera of Psyllipsocidae.